2022
DOI: 10.1007/s10898-022-01199-z
|View full text |Cite
|
Sign up to set email alerts
|

On maximum-sum matchings of points

Abstract: Huemer et al. (Discrete Mathematics, 2019) proved that for any two point sets R and B with $$|R|=|B|$$ | R | = | B | , the perfect matching that matches points of R with points of B, and maximizes the total squared Euclidean distance of the matched pairs, has the property that all the disks induced by the matching have a common point. Each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Huemer et al [6] proved that if M is any perfect matching of R and B that maximizes the total squared Euclidean distance of the matched points, i.e., it maximizes (p,q)∈M p − q 2 , then all disks of B M have a point in common. As proved by Bereg et al [2], the disks of our max-sum matching M of R ∪ B intersect pairwise, fact that will be used in this paper, but the common intersection is not always possible.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Huemer et al [6] proved that if M is any perfect matching of R and B that maximizes the total squared Euclidean distance of the matched points, i.e., it maximizes (p,q)∈M p − q 2 , then all disks of B M have a point in common. As proved by Bereg et al [2], the disks of our max-sum matching M of R ∪ B intersect pairwise, fact that will be used in this paper, but the common intersection is not always possible.…”
Section: Introductionmentioning
confidence: 88%
“…Bereg et al [2] obtained an approximation to this conjecture. They proved that for any point set P of 2n uncolored points in the plane and a max-sum matching M = {(a i , b i ), i = 1, .…”
Section: Introductionmentioning
confidence: 91%
“…In 2021, Bereg, Chacón-Rivera, Flores-Peñaloza, Huemer, Pérez-Lantero, and Seara [4,Theorem 3.14] showed that a max-sum matching of any even set in the plane is a Tverberg graph. Our second result is a new proof of a slightly stronger version of their theorem.…”
Section: Similarly a Graph Is An Open Tverberg Graph If The Open Ball...mentioning
confidence: 99%
“…To do so, we consider the set D of diametral disks of edges in M . A recent result of Bereg et al [5] combined with Helly's theorem [22,30] implies that the disks in D have a common intersection. We take a point in this intersection and connect it to endpoints of all edges of M to obtain a star S. Then we show that w(M * ) ⩽ w(S) ⩽ √ 2 • w(M ), which proves the weaker lower bound.…”
Section: Our Contributionsmentioning
confidence: 99%
“…Maximum-weight matching is among well-studied structures in graph theory and combinatorial optimization. It has been studied from both combinatorial and computational points of view in both abstract and geometric settings, see for example [1,3,5,11,9,12,13,16,17,19,24,25,31]. Over the years, it has found applications in several areas such as scheduling, facility location, and network switching.…”
Section: Introductionmentioning
confidence: 99%